Carney Triad, Carney-Stratakis Syndrome, 3PAS and Other Tumors Due to SDH Deficiency - Pitsava, Georgia; Settas, Nikolaos; Faucz, Fabio R.; Stratakis, Constantine A. (Frontiers in Endocrinology, 2021)
Succinate dehydrogenase (SDH) is a key respiratory enzyme that links Krebs cycle and electron transport chain and is comprised of four subunits SDHA, SDHB, SDHC and SDHD. All SDH-deficient tumors are caused by or secondary to loss of SDH activity. As many as half of the familial cases of paragangliomas (PGLs) and pheochromocytomas (PHEOs) are due to mutations of the SDHx subunits. Gastrointestinal stromal tumors (GISTs) associated with SDH deficiency are negative for KIT/PDGFRA mutations and present with distinctive clinical features such as early onset (usually childhood or adolescence) and almost exclusively gastric location. SDH-deficient GISTs may be part of distinct clinical syndromes, Carney-Stratakis syndrome (CSS) or dyad and Carney triad (CT). CSS is also known as the dyad of GIST and PGL; it affects both genders equally and is inherited in an autosomal dominant manner with incomplete penetrance. CT is a very rare disease; PGL, GIST and pulmonary chondromas constitute CT which shows female predilection and may be a mosaic disorder. Even though there is some overlap between CT and CSS, as both are due to SDH deficiency, CSS is caused by inactivating germline mutations in genes encoding for the SDH subunits, while CT is mostly caused by a specific pattern of methylation of the SDHC gene and may be due to germline mosaicism of the responsible genetic defect.